Changes in Extreme Rainfall Over India and China Attributed to Regional Aerosol‐Cloud Interaction During the Late 20th Century Rapid Industrialization - Lin, Lei; Xu, Yangyang; Wang, Zhili; Diao, Chenrui; Dong, Wenjie; Xie, Shang‐Ping (Geophysical research letters, 2018)
Both mean and extreme rainfall decreased over India and Northern China during 1979–2005 at a rate of 0.2%/decade. The aerosol dampening effects on rainfall has also been suggested as a main driver of mean rainfall shift in India and China. Conflicting views, however, exist on whether aerosols enhance or suppress hazardous extreme heavy rainfall. Using Coupled Model Intercomparison Project phase 5 (CMIP5) multimodel ensemble, here we show that only a subset of models realistically reproduces the late‐20th‐century trend of extreme rainfall for the three major regions in Asia: drying in India and Northern China and wetting in Southern China, all consistent with mean rainfall change. As a common feature, this subset of models includes an explicit treatment of the complex physical processes of aerosol‐cloud interaction (i.e., both cloud‐albedo and cloud‐lifetime effects), while simulation performance deteriorates in models that include only aerosol direct effect or cloud‐albedo effect. The enhanced aerosol pollution during this rapid industrialization era is the leading cause of the spatially heterogeneous extreme rainfall change by dimming surface solar radiation, cooling adjacent ocean water, and weakening moisture transport into the continental region, while GHG warming or natural variability alone cannot explain the observed changes. Our results indicate that the projected intensification of regional extreme rainfall during the early‐to‐mid 21st‐century, in response to the anticipated aerosol reduction, may be underestimated in global climate models without detailed treatment of complex aerosol‐cloud interaction. Plain Language Summary Over Asia, a robust pattern of drying‐wetting‐drying trend over three most populated regions (India, South China, and North China, respectively) have been observed in the past few decades. Yet the cause of the 30‐year trend is rather unclear, with conflicting arguments on the importance of natural variability, the greenhouse gas, land cover, and aerosols. Most of the previous studies, however, fail to provide a holistic explanation for all three major regions simultaneously. The aerosol‐cloud interaction‐induced oceanic cooling, as we show here, provides a critical piece in reproducing the past trend. Only a fraction of climate models with complex treatment of aerosol‐cloud interaction capture the observed pattern; thus, unconstrained model data set provides biased outlook of extreme rainfall in this region. Key Points Drying‐wetting‐drying trend over India, Southern China, and Northern China is observed in the last few decades of the 20th century Previous work failed to give a holistic explanation for three regions simultaneously, while this study attributes observed trend to aerosol The CMIP5 models with more complex treatment of aerosol‐cloud interaction capture the observed pattern better